2017
DOI: 10.1002/prp2.296
|View full text |Cite
|
Sign up to set email alerts
|

Magnitude and predictors of antiretroviral treatment failure among HIV-infected children in Fiche and Kuyu hospitals, Oromia region, Ethiopia: a retrospective cohort study

Abstract: The objective of the study was to assess the magnitude and predictors of first‐line antiretroviral treatment failure among HIV‐infected children. A retrospective cohort study was conducted between January 2006 and December 2015. All pediatric patients of <15 years old and who took at least 6 months of ART in Fiche and Kuyu hospitals of Oromia region, Ethiopia were included in the study. Collected data were entered and analyzed using SPSS version 20. Multivariable logistic regression was employed to identify pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
51
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(68 citation statements)
references
References 14 publications
11
51
6
Order By: Relevance
“…Studies found through databases search were done between 2005 and 2016. Eight of the studies were conducted in the Amhara region, whereas five in Addis Ababa [13,[21][22][23][24], three in Oromia [18,25,26], one in Tigray [14], and one in SNNPR [27]. Three studies were done by case-control study design [24,28,29], four studies by cross-sectional [14,[30][31][32], and eleven by cohort study design [13, 15-18, 21-23, 25-27].…”
Section: Characteristics Of Studiesmentioning
confidence: 99%
See 3 more Smart Citations
“…Studies found through databases search were done between 2005 and 2016. Eight of the studies were conducted in the Amhara region, whereas five in Addis Ababa [13,[21][22][23][24], three in Oromia [18,25,26], one in Tigray [14], and one in SNNPR [27]. Three studies were done by case-control study design [24,28,29], four studies by cross-sectional [14,[30][31][32], and eleven by cohort study design [13, 15-18, 21-23, 25-27].…”
Section: Characteristics Of Studiesmentioning
confidence: 99%
“…Three studies were done by case-control study design [24,28,29], four studies by cross-sectional [14,[30][31][32], and eleven by cohort study design [13, 15-18, 21-23, 25-27]. Ten studies were done on adult population [13, 16, 17, 21, 23-25, 28, 29, 32], six on children [15,18,22,26,27,31], and two on all age group [14,30] (Table 1).…”
Section: Characteristics Of Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…A higher viral load may leads to HIV treatment failure, which is becoming a threat of different African countries, like in Burkina Faso (6.4%) (12), Ghana (15.7%) (13), and Tanzania (14.9%) (14). In Ethiopia, virological, immunological, and clinical failure found to be in the range between 1.3% (15) to 11.5% (16), 2.1% (17) to 21% (18), and 3.1% (19) to 12.3% (20) respectively.…”
Section: Introductionmentioning
confidence: 99%